What’s Wrong with Mis-devotion? A John Donne Enigma - Huebert, Ronald (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2018)
The nominal purpose of this article is to develop a cogent and persuasive interpretation of the term “mis-devotion,” a coinage John Donne uses twice in his poems: once near the end of The Second Anniversary and once in the second stanza of “The Relic.” I also cite the two known examples of this term in Donne’s prose, from the final paragraph of Biathanatos and from a sermon he preached at St. Paul’s (21 May 1626); and I cite several closely related locutions, such as “mis-devout zeale,” from Pseudo-Martyr. On the surface, it soon becomes apparent that “mis-devotion” is always a nickname for the Roman Catholicism in which Donne was raised. But as soon as this recognition has been made, other problems of interpretation arise, many of them suggesting that “residual Catholicism” (to borrow an apt phrase from Jeanne Shami) continued to haunt his imagination. What begins as a lexical enquiry therefore ends with a speculative appreciation of how difficult it was, both personally and culturally, for Donne to repudiate the past.